Vertical integration and product differentiation - Zanchettin, Piercarlo; Mukherjee, Arijit (Elsevier, 2017)
We study a new channel of downstream rent extraction through vertical integration: competition for integration. Innovative downstream firms create value and profit opportunities through product differentiation, which however affects an upstream monopolist’s incentive to vertically integrate. By playing the downstream firms against each other for integration, the upstream firm can extract even more than the additional profits generated by the downstream firms’ differentiation activities. To preempt rent extraction, the downstream firms may then reduce differentiation, which reduces social welfare. We show that this social cost of vertical integration is more likely to arise in innovative and competitive industries, and that the competition for integration channel of downstream rent extraction is robust to upstream competition.